2017
DOI: 10.1115/1.4038050
|View full text |Cite
|
Sign up to set email alerts
|

Scenario-Based Multi-Objective Optimization of an Air-Based Building-Integrated Photovoltaic/Thermal System

Abstract: In this paper, a genetic algorithm-based multi-objective optimization of a building-integrated photovoltaic/thermal (BIPV/T) system is carried out to find the best system configurations which lead to maximum energetic and exergetic performances for Kermanshah, Iran climatic condition. In the proposed BIPV/T system, the cooling potential of ventilation and exhaust airs are used in buildings for cooling the PV panels and also heating the ventilation air by heat rejection of PV panels. Four scenarios with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Various studies have shown that placing a glass cover on PV panels results in improved thermal performance and reduced electrical performance of the PV/T collector. 16,17,25 A review of the literature reveals that the performance of glazed BIPV/T-HRW unit has not been studied so far. Therefore, our next study will be devoted to the energy and exergy analysis of the glazed BIPV/T-HRW units.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies have shown that placing a glass cover on PV panels results in improved thermal performance and reduced electrical performance of the PV/T collector. 16,17,25 A review of the literature reveals that the performance of glazed BIPV/T-HRW unit has not been studied so far. Therefore, our next study will be devoted to the energy and exergy analysis of the glazed BIPV/T-HRW units.…”
Section: Discussionmentioning
confidence: 99%
“…Kermanshah is the capital of Kermanshah province in the western part of Iran and enjoys mountainous moderate climate. The mean annual solar radiation in Kermanshah is about 7.1 GJ per square meter, and thus, it features awesome potential in sun powered vitality frameworks …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the heated fluid can be actually used in various applications depending on the form of heat energy (water or air). Many studies throughout the world have been done so far to study the performance of photovoltaic thermal (PVT) collectors by all means of analytical solutions, experimental measurements, and numerical simulations . The aim of analytical solutions is to simplify the process of performance estimation, while experimental studies provide a more realistic approach in view of the environmental and operating conditions.…”
Section: Introductionmentioning
confidence: 99%